Model Teaching History Based On The Traditional Values Singo Ulung To Increase Mutual Cooperatif Attitude Students In Senior High School Of Grujugan Bondowoso - Jefri Rieski Triyanto; Akhmad Arif Musadad; Hermanu Joebagio (ISTORIA: Jurnal Pendidikan dan Sejarah, 2018)
ABSTRAKThis research is expected to be able to foster and enhance the mutual cooperation attitude of students by imitating the values of mutual cooperation in the Singo Ulung tradition. The design development of the Singo Ulung tradition-based historical learning model is based on the ADDIE procedure Feasibility data analysis model using a Likert scale with a range of 1 to 5, while the model effectiveness test using the Independent Sample T Test T test on SPSS 19. In the T Test for achievement tests obtained a value of 2.637 with a significance level of 0.012 0.025, meaning that there is a significant to the model developed and shows that the mean of the experimental class is better than the control class. The T test for the assessment of mutual cooperation attained a value of 2.649 with a significance level of 0.011 0.025, so it can be concluded that the average of the experimental class is better than the control class. Thus, the historical learning model based on Singo Ulung traditional values is effective to improve student achievement and mutual cooperation.Keywords: value local traditions, model development, mutual cooperation